Religiosity and Proactive Coping with Social Difficulties in Romanian Adolescents - Răban-Motounu, Nicoleta (Journal of religion and health, 2015)
Even though medical and psychological sciences and services evolved so much, in many cases, the healing process has its mystery, and some recoveries seem to be entirely magical. Especially in such cases, religion seems to play an important role, as it helps people face the “mystery” of the healing process and integrate it. Religion has helped people face potentially traumatic events with minimum consequences for their health, or, moreover, to use these experiences for personal development, making them more prepared for life challenges. Adolescents with developed proactive coping skills are less socially inhibited or non-assertive, and those that are less cold/distant or more self-sacrificing have stronger spiritual values.